The Role of the Karawitan UKM in Internalizing Religious Moderation Among UIN Surakarta Students - nova linda; Kesya Najmi; Muhammad Iqbal; Nabila Salsabila; Khusnul Tri (EL- Hayah, 2025)
This study examines the role of the Karawitan Student Activity Unit (UKM) at UIN Raden Mas Said Surakarta in internalizing the values of religious moderation as a means of strengthening students' Islamic and cultural identity. Using a descriptive qualitative approach with interview techniques, the study found that the karawitan UKM not only serves as a platform for preserving traditional arts but also as a venue for character education, tolerance, and religious moderation. Karawitan activities train students to uphold harmony, cooperation, and an attitude of respecting differences and values that align with religious moderation. In addition, the integration of Islamic values in the arts, cross-faculty interaction spaces, and institutional support from the campus further reinforce students' religious and cultural identity. Nevertheless, the internalization of religious moderation still faces challenges, particularly in the limited space for interfaith dialogue and the suboptimal integration of moderation theory in student organization programs. This study emphasizes that the art of karawitan has strategic potential in shaping a campus youth generation that is moderate, inclusive, and rooted in local culture.